Are Virtual Environments the New Frontier in Obesity Management?. Issue 11 (November 2014) - Cornick, Jessica E.; Blascovich, Jim
Abstract Advances in virtual environment technology, particularly digital immersive virtual environment technology, enable people to engage in increasingly compelling experiences. Such technology not only has entertainment value but also provides a powerful research platform for behavioral scientists and clinicians. Although many immersive virtual environment‐based studies have been conducted in the last 20 years, investigations of psychological and physical health remain relatively rare. In short, virtual environment technology provides investigators and health care providers with a powerful tool to study motivate their research participants and patients to improve or regain health. Here, the nature of the technology, ideas for future research using it, and how it has and can be used to assess and combat the obesity epidemic sweeping the United States.